The Role of Family Business in Selecting Audit Quality - Titis Puspitaningrum Dewi Kartika (LPPM of NAROTAMA UNIVERSITY, 2021)
This study concerns with a descriptive analysis of the differences between family business and non-family business as seen from audit fees and audit quality. Audit quality is measured from the size of KAP and industry specialization. In addition, this study analyses the impact between family ownership on audit quality (KAP size and industry specialization). This study examines the influence of audit committee effectiveness on the audit quality. This study used logistic regression analysis. The unit of analysis in this study is the financial statements, while the population is all manufacturing companies listed on the IDX, while the sample in this study is manufacturing companies from 2014 to 2016. The results of this study states that there is no difference between family and non-family business in selecting quality. Second, there is a difference in audit fees between family and non-family business. Third, there is an influence between family ownership and audit fees. This can be interpreted that business in Indonesia which are mostly owned by families, have a very important influence on how much the audit fees incurred for independent parties. Fourth, there is an influence between family ownership and audit quality (based on KAP size). Fifth, there is an influence between family ownership and audit quality (based on industry specialization). Sixth, there is an influence between the effectiveness of the audit committee and audit quality (based on the KAP size). Seventh, there is an influence between the effectiveness of the audit committee and audit quality (based on industry specialization).